2013
DOI: 10.1071/mf12121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near-future seawater temperature rises on sea urchin sperm longevity

Abstract: Abstract. Global warming has and will continue to warm the world's oceans, which may have detrimental consequences for marine life. Studies assessing the impact of climate-change stressors on early life-stages of marine invertebrates have focussed on immediate fertilisation success or larval development, but have so far not considered gamete longevity. Recent studies have suggested that sea urchin fertilisation can take place for several hours, as dilute spermatozoa can travel to fertilise distant eggs, making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Variation in seawater temperature is characteristic of many nearshore ecosystems. Our results, covering a wide range of temperatures, showed responses that were consistent with TPCs reported for many traits from a wide array of species [110][111][112][113][114]. Although simple positive or negative responses to increasing temperatures have been reported in some echinoderms (Table 1), these results typically emerge from experiments covering a narrower thermal range…”
Section: Discussionsupporting
confidence: 89%
“…Variation in seawater temperature is characteristic of many nearshore ecosystems. Our results, covering a wide range of temperatures, showed responses that were consistent with TPCs reported for many traits from a wide array of species [110][111][112][113][114]. Although simple positive or negative responses to increasing temperatures have been reported in some echinoderms (Table 1), these results typically emerge from experiments covering a narrower thermal range…”
Section: Discussionsupporting
confidence: 89%
“…The thermal conditions during embryogenesis may provide the organism with information about anticipated environmental breeding conditions. Experiments with sea urchin Heliocidaris tuberculata sperm showed that longevity of spermatozoa decreases with increasing water temperature (Binet & Doyle 2013), and the same may hold for other organisms. Thus, a larger number of sperm cells, which travel in the water for external fertilization of the eggs, may compensate for an expected shorter activity period in warmer water.…”
Section: Discussionmentioning
confidence: 96%
“…In other squamates and mammalians, high temperatures also harm sperm dynamic, possibly through an increase in sperm metabolic rates that alters enzymes or the resistance of the lipid membrane to Reactive Oxygen Species (ROS) ( Soren et al, 2018 ; Tourmente et al, 2011b ). In ectotherm marine species, warming environments can either boost ( Ho et al, 2013 ) or harm sperm velocity ( Binet and Doyle, 2013 ). In internally fertilizing ectotherms, sperm production ( Zeh et al, 2012 ) and performance within the female tract might be negatively impacted, since sperm deteriorates rapidly after being exposed to heatwaves ( Sales et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%